Financial literacy implications for retirement security and the financial marketplace - Mitchell, Olivia S.; Lusardi, Annamaria (Oxford : Oxford University Press, 2011)
As defined contribution pensions become prevalent, retirees are increasingly responsible for managing their own pension assets and thus their own financial literacy becomes crucial. Based on empirical evidence and new research, this book examines how financial literacy enhances retirement decision-making in ever more complex financial markets.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Defined contribution pension plans; Financial literacy; Finance, Personal